STRATEGI PEMASARAN SYARIAH UMKM DALAM MEMPERTAHANKAN USAHA DI ERA REVOLUSI INDUSTRI 4.0 - Yeni Rokhilawati; Atiqatul Musyarofah; Jami’atul Aysa (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
In today's era of highly advanced development, executing marketing strategies requires adapting to the ongoing industrial revolution, which has progressed through several phases. The current phase is the Fourth Industrial Revolution (Industry 4.0), a concept introduced by the German government that aims to present a paradigm shift toward a digital future in industrial production. This study aims to explore how sharia marketing strategies are implemented by MSMEs (Micro, Small, and Medium Enterprises) to sustain their businesses in the Industry 4.0 era, with a case study on Narubi Store in Kalibaru District. This is a descriptive qualitative research using four respondents as research subjects. Data collection techniques included open observation, structured interviews, and documentation. Data analysis techniques involved data reduction, data presentation, and drawing conclusions. The validity of the data was tested through source triangulation. The findings reveal that the implementation of sharia marketing strategies by MSMEs in maintaining their business during the Industry 4.0 era at Narubi Store utilizes the 9P marketing mix, namely:1. Product: The product is marketed with full honesty, providing accurate information without exaggeration or understatement about the quality of the goods, 2. Price: Product prices reflect the actual quality of the goods being sold, 3. Place: Narubi Store is located in a strategic area that is easily accessible for both customers and couriers, 4. Promotion: Marketing is carried out through social media platforms such as Facebook, Instagram, and Shopee, 5. People (Human Resources): Employees receive training related to effective marketing techniques, 6. Process: The sales process includes greeting customers, engaging in friendly conversation, and asking what products they are looking for, 7. Physical Evidence: Internally, the store provides facilities such as a parking area, signage, and pamphlets. Externally, there is a prayer room (musholla) for employees, a toilet, uniforms for staff, business permits, and other official documentation, 8. Promise: All promises made to customers are consistently fulfilled, 9. Patience: Staff demonstrate patience in dealing with customers.